2021
DOI: 10.3390/pr9061033
|View full text |Cite
|
Sign up to set email alerts
|

A New Rotor-Type Dynamic Classifier: Structural Optimization and Industrial Applications

Abstract: Due to the inadequate pre-dispersion and high dust concentration in the grading zone of the turbo air classifier, a new rotor-type dynamic classifier with air and material entering from the bottom was designed. The effect of the rotor cage structure and diversion cone size on the flow field and classification performance of the laboratory-scale classifier was comparatively analyzed by numerical simulation using ANSYS-Fluent. The grinding process performance with an industrial classifier was also tested on-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Centrifugal pneumatic classifiers are used to separate finely dispersed materials with a particle size of not more than 50-100 µm [7]. For the separation of granular materials with a particle size of 1-4 mm, these classifiers are not suitable since they require increased energy costs for pumping air flow through the working volume of the device.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Centrifugal pneumatic classifiers are used to separate finely dispersed materials with a particle size of not more than 50-100 µm [7]. For the separation of granular materials with a particle size of 1-4 mm, these classifiers are not suitable since they require increased energy costs for pumping air flow through the working volume of the device.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Aiming at the problems of uneven material dispersion and serious wear of guide vanes, some scholars researched and designed a new rotor classifier and carried out numerical simulation and optimization of the internal structure [25][26][27]. To date, although many studies have been carried out to optimize the operating parameters, the results presented showed that there are differences in the optimum operating parameters for different classifiers and materials, and few studies have been reported on the calcined petroleum coke classification experiments.…”
Section: Introductionmentioning
confidence: 99%